Increased Let-7e expression is associated with long-term all-cause mortality and antiplatelet treatment in patients with type 2 diabetes mellitus. (14th October 2021) - Eyileten, C; Pordzik, J; Jakubik, D; Czajka, P; Wolska, M; Jarosz-Popek, J; Fitas, A; Nowak, A; De Rosa, S; Gasecka, A; Cieslicka-Kaplon, A; Siller-Matula, J; et al.
Abstract: Background: In the light of growing prevalence of type 2 diabetes mellitus (T2DM), efforts are made to discover novel biomarkers. MicroRNAs (miRNAs-miR) are non-coding RNAs used in various processes involved in regulating gene expression which play a role in platelet function. Purpose: To analyze the ability of platelet-derived miRNAs in prediction of mortality and response to antiplatelet treatment among T2DM-patients. Methods: 252 diabetic subjects were enrolled and were receiving either acetylsalicylic acid (ASA) 75mg (65%) or 150 mg (15%) or clopidogrel (19%). Plasma miR-126, miR-223, miR-125a-3p and Let-7e expressions were assessed by qRT-PCR and compared between the patients who survived and those who died. Median observation time was 5.9 years. Adjusted Cox-regression analysis was used for prediction of mortality. Differential miRNAs expression due to different antiplatelet treatment was analyzed. Results: ROC curve analysis revealed increasing concentrations of miR-126, Let-7e and miR-125a-3p levels had a diagnostic ability for prediction of long-term all-cause mortality (c-index=0.75, p<0.001; 0.72, p<0.001; 0.72, p=0.001, respectively). Multivariate Cox regression model revealed high miR-126 and Let-7e expressions which were strong and independent predictors of all-cause long-term mortality (HR=5.08, 95% CI: 1.92–13.43; p=0.001; HR=5.94, 95% CI: 1.98–17.79; p=0.001, respectively). After including all miRNAs into one multivariate Cox regression model, only Let-7e was predictive of future occurrence of long-term all-cause death (HR=7.83, 95% CI: 1.2–51.1; p=0.032). MiR-126, Let-7e and miR-223 expressions in the clopidogrel group were significantly higher than in the ASA group (p=0.014; p=0.013; p=0.028, respectively). Conclusions: Let-7e expression is a strong and independent predictor of long-term all-cause mortality among patients with T2DM. MiR-223, miR-126 and Let-7e present significant interactions with antiplatelet treatment and clinical outcomes. Funding Acknowledgement: Type of funding sources: None.